Coral Reefs: Tourism, Conservation and Management - Prideaux, Bruce; Pabel, Anja; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Coral reefs are an important tourism resource for many coastal and island destinations and generate a range of benefits to their local communities, including as a food source, income from tourism, employment and recreational opportunities. However, coral reefs are under increasing threat from climate change and related impacts such as coral bleaching and ocean acidification. Other anthropogenic stresses include over-fishing, anchor damage, coastal development, agricultural run-off, sedimentation and coral mining. This book adopts a multidisciplinary approach to review these issues as they relate to the sustainable management of coral reef tourism destinations. It incorporates coral reef science, management, conservation and tourism perspectivesand takes a global perspective of coral reef tourism issues covering many of the world$1 (Bs most significant coral reef destinations. These include the Great Barrier Reef and Ningaloo Reefin Australia, the Red Sea, Pacific Islands, South East Asia, the Maldives, the Caribbean islands, Florida Keys and Brazil. Specific issues addressed include climate change, pollution threats, fishing, island tourism, scuba diving, marine wildlife, governance, sustainability, conservation and community resilience. The book also issues a call for more thoughtful development of coral reef experiences where the ecological needs of coral reefs are placed ahead of the economic desires of the tourism industry.s
1. Coral Reef Systems as a Tourism Resource -- --Anja Pabel and Bruce Prideaux -- PART I: The ecology and governance of coral reefs -- 2. Coral Reefs: Impacts and Sustainability in the South Pacific Islands -- --Semisi Taumoepeau and Anja Pabel -- 3. Coral based tourism in Egypts Red Sea -- --Nathalie Hilmi, Alain Safa, Stphanie Reynaud and Denis Allemand -- 4. Australias Great Barrier Reef Protection, Threats, Value and Tourism Use -- --Bruce Prideaux and Anja Pabel -- 5. Strategic Caribbean Coral Reef Tourism Management -- --Dennis J. Gayle and Bernadette E. Warner -- PART II: Threats and sustainability issues facing coral reef tourism -- 6. The potential for coral bleaching to affect long-term destination sustainability -- --Bruce Prideaux, Anja Pabel, Michelle Thompson and Leonie Cassidy -- 7. Belize Barrier Reef System A Threatened Biodiversity Hotspot -- --Leandra Cho-Ricketts -- 8. Coral Reefs of the Florida Keys: The Threats of a Changing Sea -- --Roberta Atzori and Alan Fyall -- 9. Whale shark tourism at Ningaloo Reef: Successes, challenges and whats next? -- --Sarah Duffy, Roger Layton and Larry Dwyer -- PART III: Development and management of coral reef tourism activities -- 10. Ecotourism and coral reef restoration: Case studies from Thailand and the Maldives -- --Margaux Y. Hein, Fanny Couture and Chad M. Scott -- 11. Tourism and fishing in paradise: a case study of the Maldives -- --Kelsey Miller -- 12. A narrative approach to understanding recreational dive tourists experiences on coral reefs -- --Anja Pabel -- 13. Tourist satisfaction and expenditures in a reef-adjoining dolphin watching industry in Lovina, Bali Indonesia -- --Putu L Mustika, Riccardo Welters and Naneng Setiasih -- 14. Tourism development and impacts on reef conservation in Brazil -- --Fernanda de Vasconcellos Pegas, Guy Castley and Ambrozio Queiroz Neto -- 15. Impacts of vessel-based day tours on coral reefs: Observations from snorkel tours in Maui, Hawaii -- --Brooke A. Porter -- Part IV: Indigenous use, the media and the way forward -- 16. Indigenous coral reef tourism -- --Henrietta L. Marrie -- 17. Media in coral reef tourism management indications from online travel magazines -- --Anja Pabel and Glen Croy -- 18. Findings and Research Issues where to from here? -- --Bruce Prideaux and Anja Pabel
Includes bibliographical references and index.
Also available in print format.
Keywords: Coral reefs and islands -- Recreational use; Coral reef conservation; Coral reef management; Tourism; Electronic books